Combination of curcumin and piperine synergistically improves pain-like behaviors in mouse models of pain with no potential CNS side effects - Pawana Boonrueng; Peththa Wadu Dasuni Wasana; Hasriadi; Opa Vajragupta; Pornchai Rojsitthisak; Pasarapa Towiwat (BMC, 2022)
Abstract Background Curcumin and piperine are major bioactive compounds of Curcuma longa and Piper nigrum, widely consumed as spices and flock medicine. The combinational use of these plants is a common practice in Southeast Asia. Synergism between curcumin and piperine has been found in several animal models but not in periodontal disease and diabetes, and the antinociceptive interaction is still unknown. Hence, the present study aimed to assess the interaction between curcumin and piperine in pain and its potential CNS side effect profile. Methods Formalin test and in vitro LPS-stimulated RAW 264.7 macrophage cells were used to assess the synergistic interaction of curcumin and piperine in a mouse model of inflammatory pain. Tail-flick and cold plate tests were applied to determine the antinociceptive synergism between piperine and curcumin. The interaction was determined by applying isobolographic analysis. The potential CNS-side effects of the curcumin and piperine combination were also assessed using LABORAS automated home-cage behavioral analysis. Results Curcumin alone dose-dependently improved pain-like behaviors in the formalin, tail-flick, and cold plate tests with the ED50 of 71.4, 34.4, and 31.9 mg/kg, respectively. Additionally, piperine exhibited efficacy in the formalin, tail-flick, and cold plate tests with the ED50 of 18.4, 8.1, and 28.1 mg/kg, respectively. The combination of curcumin and piperine (1:1 ED50 ratio) produced synergistic interaction in the formalin, tail-flick, and cold plate tests as assessed significantly lower experimental ED50 values (5.9, 5.2, and 5.5 mg/kg) compared to theoretical ED50 values (44.9, 21.3, and 30.0 mg/kg), isobologram analysis, and interaction index values of 0.13, 0.24 and 0.18, respectively. The synergistic interaction of curcumin and piperine was further confirmed by the efficacy of the combination in LPS-stimulated RAW 264.7 macrophage cells. Curcumin and piperine interacted synergistically, reducing proinflammatory mediators. The combination also demonstrated better compatibility profiles with neuronal cells. Furthermore, the curcumin-piperine combination had no effects on mouse spontaneous locomotor behaviors in LABORAS automated home cage monitoring. Conclusion Overall, the present study demonstrates strong antinociceptive synergism between curcumin and piperine in mouse models with no potential CNS side effects, suggesting its possible use in clinical trials.